Adjunct faculty experiences in a comprehensive development program: a single-site case study - Wells, Christopher Alan, author; Timpson, William, advisor; Davies, Timothy, committee member; Kaminski, Karen, committee member; Doe, Sue, committee member (Colorado State University. Libraries, 2015)
Adjunct faculty have come to represent an increasingly larger portion of the overall faculty population in American community colleges and according to recent studies now account for approximately 70% of the instructors in these institutions. Definitions of adjunct faculty vary considerably, but they are generally part-time instructors whose course load is less than the full-time faculty requirement. There has been limited attention paid in the literature to the training and development needs of this faculty group. In addition, we know even less about the needs of the individual types or categories of adjunct or part-time faculty and their experiences in training and development programs. This study examines the experiences of a sub-set of adjunct faculty who are practicing professionals outside of higher education and who teach on a part-time basis. I have labeled this group practitioner adjunct faculty. For this study, I chose to complete a single-site case study of a part-time faculty training and development program at community college in the southeastern United States. My primary data source came from interviews with 10 practitioner adjunct faculty who had completed either the 2010 or 2011 version of the college's centerpiece course in their efforts to support and develop their part-time faculty, the Summer Certification Program. In addition to interview data, I also collected data from internal college documents and the college web site, interviews with academic and professional development leaders, and my own direct observations of training and support programs for the college's part-time faculty. The data from this study have provided an overview of the practitioner adjunct faculty study participants' perspectives on their experiences with the college's training and support efforts. The results show that while these faculty are not fully aware of and are largely not taking advantage of many of the training and support programs offered by the college, the Summer Certification Program was seen as a valuable resource by most of the study participants and does appear to have had an impact on their classroom practice.
Keywords: professional development; adjunct faculty